Parenting by men who batter new directions for assessment and intervention - Edleson, Jeffrey L.; Williams, Oliver J. (Oxford : Oxford University Press, 2007)
Beginning with the voices of mothers and fathers who speak about men's contact with and parenting of their children, the authors then examine court and mental health services perspectives on how much involvement violent men should have in their children's lives.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Family violence; Abusive men -- Counseling of; Parenting